CATEGORY SHIFTS OCCURENCE IN THE INDONESIAN TRANSLATION OF LITTLE WOMEN - Sentana, Aswarini (Universitas Gunadarma, 2015)
This is a translation study related to translation shifts occurrence in the Indonesian translation of Novel Little Women written by Louisa May Alcott. The purposes of this study are to find out what types of category shifts found in the Indonesian translation of Little Women and to find out the dominant category shift found in the translation. The method which is used by the researcher is the combination of descriptive qualitative and quantitative method. The result of the research shows that all types of category shifts which are structure shift, class shift, unit shift and-system shifts, found in the translation. It also shows that the dominant category shift found in the translation is structure shift. Keywords: Translation, Translation shifts, Category shifts.